2020
DOI: 10.1002/jccs.202000068
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted synthesis of the Fe2O3/g‐C3N4 nanocomposites with enhanced photocatalytic activity for degradation of methylene blue

Abstract: The preparation and photocatalytic performance of the Fe 2 O 3 /g-C 3 N 4 nanocomposites with different weight percentage of iron was investigated in this study. Samples were successfully synthesized using melamine and ferric nitrate as the precursors via the green and facile microwave-assisted method. The physicochemical and structural properties of the Fe 2 O 3-doped g-C 3 N 4 were characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), the Brunauer-Emmett-Teller (BET) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…It can be concluded that the bandgap of NiAl-MMO was about 3.27 eV, close to the bandgap of pure NiO in the literature, 64,65 further indicating that NiAl-MMO was mainly composed of NiO. Among the as-prepared NiO/NiC/g-C 3 N 4 samples, L1C and L5C nanocomposites showed absorption features similar to g-C 3 N 4 and NiAl-MMO, respectively.…”
Section: Structural Characterization Of Nio/nic/g-c 3 N 4 Compositessupporting
confidence: 79%
See 1 more Smart Citation
“…It can be concluded that the bandgap of NiAl-MMO was about 3.27 eV, close to the bandgap of pure NiO in the literature, 64,65 further indicating that NiAl-MMO was mainly composed of NiO. Among the as-prepared NiO/NiC/g-C 3 N 4 samples, L1C and L5C nanocomposites showed absorption features similar to g-C 3 N 4 and NiAl-MMO, respectively.…”
Section: Structural Characterization Of Nio/nic/g-c 3 N 4 Compositessupporting
confidence: 79%
“…76 The photogenerated electrons in the CB of g-C 77,78 The superoxide radical anion O 2 c À , hydroxyl radical cOH, and the holes are known as the reactive species that facilitate the degradation of the organic pollutants into harmless products like CO 2 and H 2 O. 64,79 To further detect the main reactive oxidative species in the photocatalytic process, isopropanol (IPA), triethanolamine (TEOA), and benzoquinone (BQ) were used as the scavengers for hydroxyl radicals (cOH), holes (h + ) and superoxide radicals (O 2 c À ), respectively. The scavenger dosages were determined as 10 mmol L À1 in the RhB solution of 50 mg L À1 and TC solution of 30 mg L À1 .…”
Section: The Photocatalytic Mechanism Of Nio/nic/g-c 3 N 4 Compositesmentioning
confidence: 99%
“…Generally, the degradation effect of the photocatalyst was determined by the photoinduced charge separation ability, light absorption, and adsorption capacity of the degraded substances. [ 40,41 ] From the PL results, compared with BiPO 4 , the photoinduced charge separation ability of BiPO 4 /SnO 2 composite is slightly increased. Based on the data for the photocatalytic degradation of RhB after 1 hr dark adsorption (before LED light irradiation), the RhB adsorption capacity of the samples is very close.…”
Section: Resultsmentioning
confidence: 99%
“…The removal degrees of the photodegradation of MB are 65.16%, 55.57%, 53.31%, and 58.56% after 180 min, respectively. The photocatalytic degradation mechanism can be described as following reactions (20-32) [52][53][54][55][56][57][58] and schematic illustration (Figure 8).…”
Section: Photocatalytic Properties Of C 6 0 @Znal-ldh/pvamentioning
confidence: 99%
“…The removal degrees of the photodegradation of MB are 65.16%, 55.57%, 53.31%, and 58.56% after 180 min, respectively. The photocatalytic degradation mechanism can be described as following reactions () [52–58] and schematic illustration (Figure 8). C60@ZnAlgoodbreak−LDH/PVAgoodbreak+C16H18ClN3normalSphysical adsorption. C60@ZnAlgoodbreak−LDH/PVAgoodbreak+italichνC60@ZnAlgoodbreak−LDH/PVA0.25em()egoodbreak+h+. normalH2O+normalh+·OH+normalH+. 2H2O+2h+normalH2normalO2+2H+. normalH2normalO2+2·OH. normalh++OH·OH. normalO2+normaleO2. …”
Section: Photocatalytic Properties Of C60@znal‐ldh/pvamentioning
confidence: 99%